Numerical Simulation of a Two-Dimension Ramp Inlet Flow Field - Jalal M. Jalil; Ahmed F. Kridy (Engineering and Technology Journal, 2009)
The Two-dimension ramp inlet flow field was studied with typical mode operations.Euler equations were used for solution with no special treatment required. In this work asolution algorithm based on finite difference MacCormack’s technique was developed tosolve mixed subsonic-supersonic flow problem through the external shock diffusers(ramp inlet) and it is found to be converge for supercritical and critical inlet operation.